Nonlinear Control of an Active Magnetic Bearing with Output Constraint - Danh Huy Nguyen; Tung Lam Nguyen; Manh Linh Nguyen; Huy Phuong Nguyen (Institute of Advanced Engineering and Science, 2018)
In this paper, an appropriate control strategy is proposed to handle the nonlinear dynamics ofan active magnetic bearing (AMB). The goal of the control design is to drive the AMB rotor to the origin with improved transient response. In order to achieve this task, back stepping control technique with a barrier Lyapunov function are employed to keep the tracking error trajectory inside a predefined zone to avoid possible mechanical contact between rotor and stator. Besides, a speed observer is also used since information about rotor speed is not always available. The stability of the closed-loop system is proven. The effectiveness of the proposed control strategy is verified by numerical simulations.